The evolving boundaries of defence an assessment of recent shifts in defence activities - Bellais, Renaud (Emerald, 2014)
This volume analyses several recent evolutions in global defence activities. Since the 1990s the industry has gradually repositioned because of geo-strategic transformations, spatial reorganisation, budgetary trends, and evolutions within the production of defence per se, which have disrupted its economic and social fabric. These changes widen the scope of industrial activities and modify the organization of relations between armed forces, firms and local economies as well as society. They deeply affect the footprints of defence in several dimensions and its impacts on local communities, public/private boundaries and evolving requirements of armed forces. The volume examines key features of recent and on-going transformations of defence issues from four perspectives. The first section considers those factors which are redefining the boundaries of defence, with a focus on defence economics; part two focuses on the spatial footprint of defence and its transformations and analyses the insertion of defence activities within urban landscapes; the third part analyses how armed forces manage their human resources; and the final section considers the international landscape of defence.
Keywords: Defensive (Military science) -- Economic aspects.; elektronické knihy; electronic books